A STUDY TO ASSESS THE LEVEL OF KNOWLEDGE REGARDING PREVENTING EPILEPSY AMONG NURSING STUDENTS IN SELECTED NURSING COLLEGES, KANPUR. (International Journal of Food and Nutritional Sciences, 2021)
Epilepsy is a neurological condition involving the brain that makes people more susceptible to havingrecurrent unprovoked seizures. It is one of the most common disorders of the nervous system and affectspeople of all ages, races and ethnic background